Individual loudness functions obtained by absolute magnitude estimation - MIŚKIEWICZ, A. (Archives of Acoustics, 1990)
Six subjects estimated, in individual listening sessions loudness of 1/3-octave noise band centered at 1 kHz. The results confirm that numerical estimates of loudness are unique characteristics of individual observers. In the present study no evidence for the existence of an absolute loudness scale could be observed.